Effective atomic numbers of some composite mixtures including borax - Bastug, Arif; Gurol, Ali; Icelli, Orhan; Sahin, Yusuf (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Effective atomic numbers for (PbO and Na(2)B(4)O(7)10H(2)O) and (UO(2)(NO(3))(2), and Na(2)B(4)O(7)10H(2)O) mixtures against changing contents of PbO, Na(2)B(4)O(2)10H(2)O, and UO(2)(NO(3))(2) were measured in the X-ray energy range from 25.0 to 58.0 keV. The gamma rays emitted by a (241)Am annular source have been sent on the absorbers which emits their characteristic X-rays to be used in transmission arrangement. The X-rays were counted by a Si(Li) detector with a resolution of 146 eV at 5.90 key. The changing compositions of the compounds were assigned to be 0, 0.167, 0.333, 0.500, 0.666, 0.833 and total masses of the mixtures were adjusted to be identical. Also, the total effective atomic numbers of each mixture were estimated by using the mixture rule. The measured values were compared with estimated values for the mixtures. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Mass attenuation coefficients; Effective atomic number; Boron compounds; Shielding materials; RAY ATTENUATION COEFFICIENTS; BORON-COMPOUNDS; TRANSMISSION EXPERIMENTS; INTERNATIONAL-UNION; ELECTRON-DENSITIES; ABSORPTION EDGES; CROSS-SECTIONS; ENERGY REGION; GLASSES; CRYSTALS; Nuclear Science & Technology